Possible seismo-ionospheric anomalies associated with the 2016 Mw 6.5 Indonesia earthquake from GPS TEC and Swarm satellites - Khan, Abdul Qadeer; Ghaffar, Bushra; Shah, Munawar; Ullah, Irfan; Oliveira‐Júnior, José Francisco; Eldin, Sayed M. (Frontiers in Astronomy and Space Sciences, 2022)
Ionospheric anomalies through satellites can provide useful information about the forthcoming earthquake (EQ) over the epicentral regions. In this paper, we investigate seismo-ionospheric anomalies associated with the Mw 6.5 Sumatra, Indonesia that occurs on 06 December, 2016 at UT (22:03). We analyzed the Total Electron Content (TEC) from Global Positioning System (GPS) signals received at the nearby stations around the epicenter. Furthermore, we also studied the TEC in local daytime and nighttime from Swarm satellites to confirm the EQ induced ionospheric perturbations. The TEC show significant perturbation within 5-10 day before the main shock in the form of positive anomalies beyond the upper bound. Similarly, Swarm satellites also validate the anomalies observed in GPS TEC from nearby operating stations within 5-10 day over the epicentral region. The geomagnetic indices were quiet for the observed TEC anomalies within 5-10 day before the main shock having Dst≤-40nt and Kp ≤ 3. This study reveals the legitimate anomalies mainly associated with the EQ and suggest to use the TEC from GPS and other satellites for possible future precursor with more equipped satellite cluster.